Oncologic and reproductive outcomes of fertility-sparing surgery for borderline ovarian tumors: first presentation of 10-year experience from a Serbian referral center - Likić Lađević, Ivana; Nešić, Dejan; Stefanović, Aleksandar; Kadija, Saša; Vilendečić, Zoran; Pilić, Igor; Dotlić, Jelena; Radojević, Miloš; Milošević, Branislav; Stefanović, Katarina (Archives of Biological Sciences, 2022)
Paper description: Most borderline ovarian tumor patients are motivated to preserve fertility, with the safety and reproductive outcomes of fertility-sparing treatment being of concern. Medical records of stage I borderline ovarian tumors treated and followed up in our institution for 10 years were analyzed. In total, 52 patients were followed for a mean of 73.42 months, out of which 45 underwent fertility-sparing treatment. The overall survival rate was 100%. The recurrence rate was 7.7%; 64.4% attempted to achieve pregnancy, and the pregnancy success rate was 44.8%. The fertility-sparing treatment in stage I borderline ovarian tumor is safe with a satisfactory oncological and reproductive outcome. Abstract: The study aimed to assess the oncologic and reproductive outcome of fertility-sparing treatment of stage I borderline ovarian tumors (BOTs). A retrospective study of patients aged 18-40 years with stage I BOTs surgically treated during a 10-year period was conducted. In total, 52 patients (average age 32.7+/-5.9) were followed for 16 to 137 months after BOT diagnosis (mean 73.4 months). The overall survival rate was 100%. Recurrence was registered in 4 patients (7.7%). All patients underwent a unilateral salpingo-oophorectomy and all histologic findings corresponded with primary BOTs (3 serous; 1 endometrioid). Higher parity increased while the histological type and stage did not impact recurrence. Average recurrence-free survival was 36.2+/-23.6 months regardless of histological type and stage. Recurrence occurred during the first 3 postoperative years in 75% of cases. Out of 45 women treated with fertility-sparing surgery, 64.4% attempted pregnancy and the pregnancy success rate was 44.8%. Only one pregnancy was conceived by assisted reproduction, while all others were spontaneous. The fertility-sparing treatment in stage I borderline ovarian tumors can be a safe and successful option both in terms of oncologic and reproductive outcomes, regardless of patient and treatment characteristics. Pregnancies after BOT surgery can be achieved with satisfactory rates and adequate outcomes.